2013
DOI: 10.1108/13527601311296238
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs on “avoidant cultures” in two French multinational corporations

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…France is no exception to this general trend. We have identified that French MNCs have used both PCNs and HCNs in subsidiaries for various reasons, which is in line with the reasons identified by earlier researchers (Hong and Doz ; Lee ). The tasks of executives may vary by multinational according to the size of operations, the business strategy they adopt in the subsidiary operations, the market size, and so on.…”
Section: Literature Reviewsupporting
confidence: 89%
“…France is no exception to this general trend. We have identified that French MNCs have used both PCNs and HCNs in subsidiaries for various reasons, which is in line with the reasons identified by earlier researchers (Hong and Doz ; Lee ). The tasks of executives may vary by multinational according to the size of operations, the business strategy they adopt in the subsidiary operations, the market size, and so on.…”
Section: Literature Reviewsupporting
confidence: 89%
“…Yet others have more recently argued that the theoretical weaknesses of cultural distance can be attenuated through the identification of moderators or considering the mechanisms by which it relates to other constructs—an approach we use in this study (Zaheer, Schomaker, & Nachum, ). We also address the problem that most previous research examines only one aspect of cultural distance at a time (e.g., Hemmasi & Downes, ) or in a specific country (e.g., Lee, ; Pelled & Xin, ), which can make generalizations more difficult (Franke & Richey, ). We also improve face validity, as most studies do not capture actual supervisor, peer, or subordinate ratings, but use same source data to assess the expatriates’ “perceptions” of the “value congruence” between leaders’ home‐country cultures and host‐country cultures (Van Vianen, Pater, Kristof‐Brown, & Johnson, ).…”
mentioning
confidence: 99%